Histological and radiographic assessment of the regenerative potential of sodium hexametaphosphate (SHMP) as a novel direct pulp capping material in an animal model - Mostafa Kamel Mohamed; Mohamed Abdelfattah Abdelrahman; Abdel-Razik Hashem Abdel-Razik; Ahmad Abdel Hamid Elheeny (BMC Oral Health)
Abstract Background This study aimed to assess the histological and radiographic effects of sodium hexametaphosphate (SHMP) as a direct pulp capping (DPC) agent in immature permanent dog premolars. Methods A split-mouth design was employed with three healthy 4-month-old Mongrel dogs, each having 36 premolars. The premolars were randomly assigned to either SHMP or MTA. The specimens were stained with hematoxylin and eosin (H&E) and Masson’s trichrome, and histologically examined three months after the animals were sacrificed. To assess root maturity, radiographic changes in root length (RL), root surface area (RSA), and apical foramen width (AFW) were measured at baseline and after 3 months. Quantitative data were analyzed using the paired-sample t-test, while the qualitative data based on Stanley's histological scoring system were tested using the Monte Carlo exact test. The level of significance was set at 5%. Results Histological findings showed no significant differences between the two groups, except for the average thickness of the predentin and odontoblastic layers, which was significantly higher in the SHMP specimens (P < 0.0001). The frequencies of fully calcified dentin bridges and regularly arranged dentinal tubules were significantly higher in the SHMP specimens (P < 0.05). Both materials showed comparable radiographic measurements (P > 0.05), except for the change in RL, which was significantly longer in the SHMP group (P < 0.05). Conclusions There were no significant differences between SHMP and MTA in some respects. Histological evaluation showed that SHMP provided better bioinductive and biocompatible properties compared to MTA. Radiographically, both materials showed comparable root maturogenesis outcomes, except for the significant increase in RL in the SHMP group. SHMP may be a suitable alternative material for DPC in the treatment of immature permanent teeth.